Does the E-Commerce City Pilot Reduce Environmental Pollution? Evidence From 265 Cities in China - Zhang, Zhixin; Sun, Zhenya; Lu, Hang (Frontiers in Environmental Science, 2022)
In order to promote the healthy and rapid development of e-commerce, China launched the construction of National E-commerce demonstration Cities in 2009. This paper presents a feasible road to achieving sustainable development through the new urban development model. The paper employs the data of 265 cities in China from 2007 to 2016 as a research sample and use the Multi-period DID method to test the impact of National E-commerce demonstration Cities pilots on urban environmental pollution. The basic result shows that urban environmental pollution reduces by about 17.5% on average after becoming pilot cities, and the National E-commerce demonstration Cities policy significantly reduces urban environmental pollution. We adopt a series of robustness tests and all tests show that the basic result is still robust. Moreover, heterogeneity tests show that the pollution reduction effect of the National E-commerce demonstration Cities policy in big cities is stronger than in small and mid-sized cities, and there is no significant difference between the eastern cities and mid-western cities. The pollution reduction effect of the National E-commerce demonstration Cities policy is more significant in cities with high human capital, low fiscal expenditure and high information infrastructure. The empirical results of spatial Dubin model show that the pilot city has no significant spatial spillover to neighboring cities. In the era of rapid development of e-commerce, this study provides a reference for developing countries to improve the urban environment and achieve sustainable development by using the new urban development model integrating e-commerce and urbanization.